Rapid radiocarbon ((14)C) analysis of coral and carbonate samples using a continuous-flow accelerator mass spectrometry (CFAMS) system - McIntyre, Cameron P.; Roberts, Mark L.; Burton, Joshua R.; McNichol, Ann P.; Burke, Andrea; Robinson, Laura F.; von Reden, Karl F.; W. J. Jenkins (Paleoceanography, 2011)
Radiocarbon analyses of carbonate materials provide critical information for understanding the last glacial cycle, recent climate history and paleoceanography. Methods that reduce the time and cost of radiocarbon ((14)C) analysis are highly desirable for large sample sets and reconnaissance type studies. We have developed a method for rapid radiocarbon analysis of carbonates using a novel continuous-flow accelerator mass spectrometry (CFAMS) system. We analyzed a suite of deep-sea coral samples and compared the results with those obtained using a conventional AMS system. Measurement uncertainty is
id: 1915; PT: J; UT: WOS:000296649300001